WS-BPEL 2.0 beginner's guide : design and develop WS-BPEL executable business processes using Oracle SOA Suite 12c /: design and develop WS-BPEL executable business processes using Oracle SOA Suite 12c. (2014) - Juric, Matjaz B; Weerasiri, Denis
No abstract available